Reconsidering “Critical” Bone Loss in Shoulder Instability: 17-Year Follow-Up Study following Arthroscopic Bankart Repair - Lawrence Chun-Man Lau; Wai-Wang Chau; Randy Ng; Jonathan Patrick Ng; Elvis Chun-Sing Chui; Michael Tim-Yun Ong; James Francis Griffith; Patrick Shu-Hang Yung (Advances in Orthopedics)
Background. Glenoid bone loss is a risk factor leading to the failure of arthroscopic Bankart repair. While 20–25% glenoid bone loss has long been considered the level to necessitate bony augmentation, recent studies indicate that 13.5% has a “subcritical” glenoid bone loss level, which is associated with decreased short- and medium-term functional scores. Few researchers worked on the long-term effect of “subcritical” or even less severe degrees of glenoid bone loss on redislocation rates and functional outcomes after arthroscopic Bankart repair. This study aimed to evaluate the effect of subcritical or less severe glenoid bone loss on redislocation rates and function after arthroscopic Bankart repair. Methods. A patient cohort who had undergone computed tomography (CT) of glenoid bone loss and arthroscopic Bankart repair over 15 years ago was reviewed. Western Ontario Shoulder Instability (WOSI) score, Single Assessment Numeric Evaluation (SANE) score, redislocation after operation, mechanism of recurrence, and revision details were reviewed. Results. Seventy-five patients were reassessed 17.6 ± 1.9 years following initial surgery. The age at enrolment was 26.8 ± 8.3 years. Twenty-two (29%) patients of the 75 patients had a redislocation on long-term follow-up, though this was not related to glenoid bone loss severity. The impaired functional score was found in patients with initial glenoid bone loss of 7% or more on long-term follow-up: WOSI (physical symptoms): 0.98 ± 2.00 vs 2.25 ± 4.01, p=0.04 and WOSI (total): 0.79 ± 1.43 vs 1.88 ± 3.56, p=0.04. Conclusions. At a mean of 17.5 years following arthroscopic Bankart repair, redislocation occurs in over a quarter of 75 patients, and they are not related to initial glenoid bone loss severity. Impaired functional outcome is apparent in patients with initial glenoid bone loss of >7%, though this impairment does not seem sufficiently severe to warrant an alternative treatment approach.